2012
DOI: 10.1038/jid.2011.426
|View full text |Cite
|
Sign up to set email alerts
|

Shining a Light on Xeroderma Pigmentosum

Abstract: Xeroderma pigmentosum (XP) is a rare, autosomal recessive disorder of DNA repair characterized by sun sensitivity and ultraviolet (UV) induced skin and mucous membrane cancers. Described in 1874 by Moriz Kaposi in Vienna, nearly 100 years later James Cleaver in San Francisco reported defective DNA repair in XP cells. This eventually provided the basis for a mechanistic link between sun exposure, DNA damage, somatic mutations and skin cancer. XP cells were found to have defects in 7 of the proteins of the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
512
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 460 publications
(528 citation statements)
references
References 86 publications
(108 reference statements)
5
512
0
11
Order By: Relevance
“…Consequences: frameshifts, protein truncations, and functional relevant amino-acid substitutions. [1][2][3] XPB/ERCC3: eight known disease-causing mutations from five patients. Mutations: 1 (12.5%) C4A transversion, 1 (12.5%) A4C transversion, 1 (12.5%) G4A transition, 3 (37,5%) T4C transitions, 1 (12.5%) deletion (c.807-808delT_T), and 1 (12.5%) insertion (c.1421-1422insA).…”
Section: Mutational Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…Consequences: frameshifts, protein truncations, and functional relevant amino-acid substitutions. [1][2][3] XPB/ERCC3: eight known disease-causing mutations from five patients. Mutations: 1 (12.5%) C4A transversion, 1 (12.5%) A4C transversion, 1 (12.5%) G4A transition, 3 (37,5%) T4C transitions, 1 (12.5%) deletion (c.807-808delT_T), and 1 (12.5%) insertion (c.1421-1422insA).…”
Section: Mutational Spectrummentioning
confidence: 99%
“…Consequences: functional relevant amino-acid substitutions, frameshifts/protein truncations. [1][2][3] XPG/ERCC5: 25 known disease-causing mutations from 19 patients. Mutations: 12 (48%) transitions, 5 (20%) transversions, and 8 (32%) deletions.…”
Section: Mutational Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 At the National Institutes of Health (NIH), we have examined XP patients since 1971 and TTD patients since 2001 as part of a natural history protocol. 7,13 Our review of all English-language-published case reports of TTD patients found 112 TTD patients, of whom 55% had abnormal characteristics at birth and 28% had maternal pregnancy complications. 14 We then conducted two molecular epidemiological studies of pregnancy and neonatal abnormalities in mothers of TTD patients in our clinic.…”
Section: Introductionmentioning
confidence: 99%
“…17 These patients had mutations in at least 8 different genes involved in nucleotide excision repair and polymerase function. 7 In order to determine the influence of the XPD gene, we now have conducted a molecular epidemiological study of pregnancy and neonatal abnormalities in the mothers of the XP patients with XPD mutations in our protocol. We compared these new data to that of the mothers of the TTD patients with XPD mutations from our earlier studies 15,16 and found large differences.…”
mentioning
confidence: 99%